2012
DOI: 10.1002/j.2161-0045.2012.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the School Counselor Repertoire Through STEM‐Focused Career Development

Abstract: The call to generate increased student interest in math and science careers continues to receive tremendous amounts of national attention, most recently in President Barack Obama's (2011) State of the Union address when he referred to the current climate as “our generation's Sputnik moment.” Responses to this call focus predominantly on teacher training and standards‐based instruction. However, considering the explosive momentum within science, technology, engineering, and mathematics (STEM) education initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 21 publications
3
30
0
2
Order By: Relevance
“…Research on institutional factors Seymour and Hewitt (1997) identified disappointment with engineering as one of the major factors leading students to drop out. Other researchers have reached similar conclusions and attributed this disappointment to poor teaching and mentoring (Marra, Rodgers, Shen, & Bogue, 2012;Nyquist et al, 1999), inadequate advising (Prieto et al, 2009;Schmidt, Hardinge, & Rokutani, 2012;Sutton & Sankar, 2011), and an unwelcoming culture in engineering departments (Duncan & Zeng, 2005). Haag et al (2007) found poor academic and career advising, unapproachable faculty members, and complicated engineering curricula to be important institutional factors contributing to attrition of students.…”
Section: Stem and Engineeringmentioning
confidence: 84%
“…Research on institutional factors Seymour and Hewitt (1997) identified disappointment with engineering as one of the major factors leading students to drop out. Other researchers have reached similar conclusions and attributed this disappointment to poor teaching and mentoring (Marra, Rodgers, Shen, & Bogue, 2012;Nyquist et al, 1999), inadequate advising (Prieto et al, 2009;Schmidt, Hardinge, & Rokutani, 2012;Sutton & Sankar, 2011), and an unwelcoming culture in engineering departments (Duncan & Zeng, 2005). Haag et al (2007) found poor academic and career advising, unapproachable faculty members, and complicated engineering curricula to be important institutional factors contributing to attrition of students.…”
Section: Stem and Engineeringmentioning
confidence: 84%
“…To become more aware of 21st‐century STEM career opportunities, CDPs should also increase their STEM literacy by learning about STEM employment trends and opportunities (Schmidt, Hardinge, & Rokutani, ). Readers may refer to the STEM Career website (http://www.stemcareer.com; Graham, ) and the Quick STEM Careers Guide (Shatkin, ) as resources for promoting STEM careers across primary, secondary, and postsecondary levels.…”
Section: A Multicultural Stem‐focused Career Interventions Frameworkmentioning
confidence: 99%
“…To become more aware of 21st-century STEM career opportunities, CDPs should also increase their STEM literacy by learning about STEM employment trends and opportunities (Schmidt, Hardinge, & Rokutani, 2012). Readers may refer to the STEM Career website (www.stemcareer.…”
Section: Framework For Multicultural Stem-focused Career Interventionmentioning
confidence: 99%
“…The capacity of the United States to produce the next wave of technological innovations is also compromised by the fact that the educational system is not producing and retaining a sufficient number of STEM-related workers, researchers, and technicians (Business Higher Education Forum, 2005;Maltese & Tai, 2011;Schmidt, Hardinge, & Rokutani, 2012). The capacity of the United States to produce the next wave of technological innovations is also compromised by the fact that the educational system is not producing and retaining a sufficient number of STEM-related workers, researchers, and technicians (Business Higher Education Forum, 2005;Maltese & Tai, 2011;Schmidt, Hardinge, & Rokutani, 2012).…”
mentioning
confidence: 99%